National Health Service : The Government's Policy (White Paper)
1944-01-03 1944 1940s 5 pages -4- contracts with voluntary hospitals. More consultants will be needed and better distribution. Changes in the consultant attachment to hospitals are contemplated with "more regular attendance and duties". Proper adequate and regular remuneration will be essential, full-time or part-time. The terms and conditions of consultant appointments will be matters for the hospitals, voluntary or municipal engaging the specialist but some control is envisaged to prevent "in breeding" or institutional partisanship or nepotism. ADMINISTRATION (A) - CENTRAL. The National Health Service will be the central responsibility of the Ministers (the Minister of Health and the Secretary of State for Scotland). They will have at their disposal - (a) The Central Medical Board - for medical service matters (pay, conditions of service, distribution of doctors) - a mainly medical body of executive officers for administration. (b) A Central Health Services Council. This will be a mixed body of health service experts of different types, not only medical but other experts in other technical issues bearing on health questions. This will be a statutory body, consultative and advisory, not only on questions submitted to it by the Minister but on matters raised by its own members. An annual report will be submitted yearly to Parliament. Experts in many medical specialities, hospital representatives, (both voluntarily and publicly owned), experts of ancillary services, will be appointed to the number of 30 to 40, after consultation with professional bodies on this Council which will select its own Chairman, the Minister providing the Secretarial expenses from public funds. Similarly, local Health Service Councils will be formed. (B) - LOCAL. Some local government changes are necessary as there will be larger area bodies - to be known as Local Joint Authorities, with representatives of County Councils and County Boroughs, acting in combination, for this special purpose of area health and hospital services. So Joint Health Boards will be set up to administer the service, and also to prepare "a rational and effective plan for all branches of the Health Service", to cover the whole range of such services, with interlocking so as to obtain National coherence, uniformity and unity. MEDICAL ADMINISTRATION Medical Administration will be by a Central Medical Board which will centrally organise the general practitioner service and arrange terms and conditions of service and remuneration for doctors contracting for work in the service. Remuneration will be from public funds (as no personal charge will be made to the patient), and so the Minister is responsible. The Minister will appoint a Central Medical Board for administration of the Practitioner Service. The Board will be the employer of the doctors, arranging contracts of different types, e.g. for providing, maintaining and staffing health centres as well as group practice contracts. 292/847/2/97